The Rescue Actions of Gembrong Goat from Extinction as Local Genetic Resources in Bali, Indonesia - Atmoko, Bayu Andri (2018)
Indonesia has several goat germplasms as local genetic resources, each of them has their own different characteristics appropriate to their natural spreading areas. Gembrong goat is one of the most critical and endangered populations of Indonesian indigenous goat breeds. The Gembrong goats are raised in Karangasem, Bali and have important roles in their rural agricultural system, not only in a socio economic but also socio-culture. Based on the report of the World Watch List for Domestic Animal in 1997, their population was 100 heads, while it is currently less than 50 heads. Conservation of Gembrong goats is urgently required, because their population decreased annually. The extinction and loss of genetic material are irreplaceable. This paper summarized of some researchs and concrete actions by universities as conservation effort for Gembrong goats. Gembrong goat conservation efforts were started in 2014, by the collected the population data and identified of phenotypic characteristics. The research found that the population of Gembrong goats in Bali were only 26 heads, consisted 10 heads of male and 16 heads of female. New Population of Gembrong goat has been intensively developed (ex situ conservation) in Pacet, East Java and Sei-Putih, North Sumatra. In the following year, conserving of the animal genetic material through out the semen cryopreservation to improve the population is carried out, because the increasment of the population with natural mating is very slow and having problems, especially the lack of adult male. Therefore, mating arrangement using frozen semen through the Artificial Insemination (AI) is best action. The last rescue action by doing the grading-up through combining natural mating and AI between Gembrong Goat with Etawah Crossbreds to produce Gembrong Etawah goats. The results of those rescue actions have not successful and satisfactory yet, there are still many problems. The rescue actions of Gembrong goat should be continuously maintained to protect local genetic resources.